Endogenous limits on proposal power - Daniel Diermeier; Pohan Fong (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2008)
We present a dynamic model of legislative bargaining in which policy making proceeds until the proposer has no more incentive to make a new proposal to replace the previously approved policy. We characterize stationary Markov perfect equilibria for the game and show that in all pure-strategy equilibria, a majority of voters without proposal power have an incentive to protect each others' benefits to secure their own long-term bargaining positions in the legislature. As a consequence, the value of proposal power is constrained.
Keywords: 330